Asociaciones entre fortalezas del carácter y satisfacción con la vida: un estudio con universitarios (2016)
The aim of the study was to identify the relationship between character strengths and life satisfaction and the mean differences between participants’ gender and age. The sample consisted of 186 college students, 62.9% women, aged 17 to 45 years (M=21.55; SD=4.79), from two Brazilian states. The instruments used were the Character Strengths Scale and the Life Satisfaction Scale. Results showed significant differences for gender, and women obtained the highest scores in four character strengths. The age of participants did not show significant differences. Regarding the correlations among the constructs studied results showed that vitality, gratitude, hope, perseverance and love were the strengths presenting the highest correlation with life satisfaction, in moderate magnitudes. Findings indicated that individuals with higher scores in hope, vitality, gratitude, love, curiosity, perseverance and social intelligence strengths, tend to live a more satisfying life.